China's Gray Zone Strategy in the South China Sea: Tactics, Objectives, and Regional Implications - Sarjito, Aris (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
This research examines China's tactics in its South China Sea gray zone strategy, contrasting them with conventional military tactics, identifying primary objectives, aligning with regional and global ambitions, and highlighting potential regional implications. This study utilizes secondary data, including academic articles, government reports, and policy papers, to analyze China's gray zone strategy in the South China Sea. Qualitative content analysis will be employed to identify and interpret themes related to tactics, objectives, and regional implications. The research findings reveal that China's gray zone strategy in the South China Sea involves tactics such as maritime militia, island-building, coercive diplomacy, and lawfare. These tactics differ from conventional military approaches as they allow China to assert control without overtly crossing the threshold of armed conflict. The primary objectives pursued by China through the implementation of a gray zone strategy in the South China Sea include securing territorial claims, enhancing regional influence, and safeguarding national security interests. These objectives align with China's larger ambitions of regional hegemony and global leadership. Potential regional implications of China's gray zone strategy encompass heightened territorial disputes, compromised regional security, restricted freedom of navigation, challenges to international law, and strained US-China relations. To manage and counterbalance the risks arising from China's gray zone strategy, affected nations and regional stakeholders should adopt strategies and policies such as strengthening regional alliances, increasing military presence, engaging in multilateral negotiations, promoting international law, and enhancing security cooperation. These measures can help preserve regional stability and safeguard the interests of the affected nations.